A Common Family Factor Underlying Language Difficulties and Internalizing Problems: Findings From a Population-Based Sibling Study. (September 2020) - Helland, Siri Saugestad; Røysamb, Espen; Brandlistuen, Ragnhild Eek; Melby-Lervåg, Monica; Gustavson, Kristin
Studies have identified concurrent, longitudinal, and bidirectional associations between language difficulties and internalizing problems. This is commonly explained by social exclusion or withdrawal from peers, but underlying mechanisms are not well understood. This study uses sibling data to investigate if the comorbidity between language difficulties and internalizing problems is best explained by familial factors shared by siblings, such as genes or family environment, or nonfamilial factors specific to each child, such as peer environment. Data include 5, 568 siblings at 5 years and 3, 654 siblings at 8 years participating in the Norwegian Mother, Father and Child Cohort Study (MoBa). We constructed a latent factor model at 5 and 8 years, including a family comorbidity factor capturing correlations between language and internalizing problems that were equally strong between as within siblings. Results showed that the correlation between one sibling's internalizing problems and the other sibling's language problems was mostly accounted for by a family comorbidity factor. The best-fitting longitudinal model included stability of the family comorbidity factor and stability of language and internalizing problems within each sibling and no cross-sibling or cross-trait longitudinal associations. This suggests that the association between language and internalizing problems may be best explained by family factors.